Sequences of the 5S rRNAs of the thermo-acidophilic archaebacterium Sulfolobus solfataricus (Caldariella acidophila) and the thermophilic eubacteria Bacillus acidocaldarius and Thermus aquaticus. - Dams, E (1983)
We have determined the nucleotide sequences of the 5 S rRNAs of three thermophilic bacteria: the archaebacterium Sulfolobus solfataricus, also named Caldariella acidophila, and the eubacteria Bacillus acidocaldarius and Thermus aquaticus. A 5 S RNA sequence for the latter species had already been published, but it looked suspect on the basis of its alignment with other 5 S RNA sequences and its base-pairing pattern. The corrected sequence aligns much better and fits in the universal five helix secondary structure model, as do the sequences for the two other examined species. The sequence found for Sulfolobus solfataricus is identical to that determined by others for Sulfolobus acidocaldarius. The secondary structure of its 5 S RNA shows a number of exceptional features which distinguish it not only from eubacterial and eukaryotic 5 S RNAs, but also from the limited number of archaebacterial 5 S RNA structures hitherto published. The free energy change of secondary structure formation is large in the three examined 5 S RNAs.